모바일 컴퓨팅 플랫폼을 이용한 SDR 기반 MOBILE WIMAX 수신기 구현 - 김한택; 안치영; 김준; 최승원; Kim, Han Taek; Ahn, Chi Young; Kim, June; Choi, Seung Won ((사)디지털산업정보학회 논문지, 8(1), 2012)
This paper implements mobile Worldwide Interoperability for Microwave Access (WiMAX) receiver using Software Defined Radio (SDR) technology. SDR system is difficult to implement on the mobile handset because of restrictions that are computing power and under space constraints. The implemented receiver processes mobile WiMAX software modem on Open Multimedia Application Platform (OMAP) System on Chip (SoC) and Field Programmable Gate Array (FPGA). OMAP SoC is composed of ARM processor and Digital Signal Processor (DSP). ARM processor supports Single Instruction Multiple Data (SIMD) instruction which could operate on a vector of data with a single instruction and DSP is powerful image and video accelerators. For this reason, we suggest the possibility of SDR technology in the mobile handset. In order to verify the performance of the mobile WiMAX receiver, we measure the software modem runtime respectively. The experimental results show that the proposed receiver is able to do real-time signal processing.